The relationship of the GDR to the World Bank Group - Wilhelm Bruns (Intereconomics, 1975)
In the World Bank's last annual report the Federal Republic of Germany was described as a leading member of the World Bank Group (IBRD, IFC and IDA). The Federal Republic has subscribed about 1.4 bn to the capital of the World Bank and to date contributed 1.1 bn to IDA. The second German state, the German Democratic Republic (GDR), on the other hand, is taking a negative attitude to the World Bank Group. Why does it do so?
Keywords: 330; World Bank